2004
DOI: 10.1109/tmag.2004.832165
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Parallel Coupled Soft Under Layers for High-Density Perpendicular Recording

Abstract: A promising soft magnetic under layer (SUL) structure consisting of anti-parallel coupled soft layers (APS) is investigated to improve the performance of high-density perpendicular recording media. CoCrPt-O recording media with average grain diameter 6 nm, coercivity of 5 kOe and nucleation field of 2 kOe is fabricated on both conventional SUL and APS. Wide-area adjacent track erasure (ATE) is observed for conventional SUL, which increases at lower interlayer spacing ( ). APS structure enables the suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…The excellent recording performance of media is due to combination of good microstructural and magnetic properties such as-small grain size, square hysteresis loops, low noise, high anisotropy, and improved thermal stability-among others [1][2][3][4][5][6][7]. Compared to the previous generation of HDD that used longitudinal recording media with random inplane crystallographic texture, a key requirement for the HDD based on perpendicular recording media is in the substantial degree of out-of-plane crystallographic texture that is necessary to achieve high signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent recording performance of media is due to combination of good microstructural and magnetic properties such as-small grain size, square hysteresis loops, low noise, high anisotropy, and improved thermal stability-among others [1][2][3][4][5][6][7]. Compared to the previous generation of HDD that used longitudinal recording media with random inplane crystallographic texture, a key requirement for the HDD based on perpendicular recording media is in the substantial degree of out-of-plane crystallographic texture that is necessary to achieve high signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The thick SUL introduces spike noise and wide adjacent track erasure (WATE). To avoid these problems, the SUL with synthetic antiferromagnetic (SAF) coupled structure have been widely used [1][2][3] as following reasons [4]; 1) Néel walls are formed in the top and bottom soft magnetic (SM) layers in a pair [5], which is effective for suppression of spike noise, and 2) Low susceptibility are realized when the angle of applied field is slightly tilted from the film normal, which can efficiently restrain WATE. We have already reported that large flopping field (H f ) appeared for (Fe 65 Co 35 ) 88 B 12 (30nm)/ Ru/ (Fe 65 Co 35 ) 88 B 12 (30 nm) stacked SUL at the 1st peak with Ru spacer thickness (d Ru ) of 0.3 nm due to the extremely large unidirectional interlayer coupling energy J 1 of 1.9 erg/cm 2 as a result of composition dependence of SM materials [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There are many advantages of perpendicular system over longitudinal system, due to the interaction effect between SUL and recording layer, such as higher writing field, read-back signal amplitude, and lower noise [1,2]. Various SUL structures such as exchange bias type [3,4] and synthetic antiferromagnetic coupling type [5,6] have been introduced to suppress the SUL induced medium noise. Generally, with increasing SUL thickness, the H k is decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Although the SUL thickness of PMR media with a shielded pole head is below 70 nm, the higher H k value of SUL is necessary to achieve higher signal to noise ratio (SNR) [7]. Nowadays, the synthetic type SUL, which is composed of FM (Ferromagnetic Layer)/Ru/FM, is used as a typical structure of SUL because of its lower noise and PW 50 during reading process [5]. In this paper, we propose the new type SUL structure, which can aid to get higher SNR and lower SUL noise.…”
Section: Introductionmentioning
confidence: 99%